2015
DOI: 10.1186/s12909-015-0452-9
|View full text |Cite
|
Sign up to set email alerts
|

Is a picture worth a thousand words: an analysis of the difficulty and discrimination parameters of illustrated vs. text-alone vignettes in histology multiple choice questions

Abstract: BackgroundAdvances in cognitive load theory have led to greater understanding of how we process verbal and visual material during learning, but the evidence base with regard to the use of images within written assessments is still sparse. This study examines whether the inclusion of images within the stimulus format of multiple choice questions (MCQs) has a predictable or consistent influence on psychometric item properties, such as difficulty or discrimination.MethodsItem analysis data from three consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…Finally, Holland et al () examined items in a histology course that utilized images and found no significant difference in difficulty or discrimination. Like the previously discussed study, they used images as part of the question stem that had to be interpreted to arrive at a correct answer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Holland et al () examined items in a histology course that utilized images and found no significant difference in difficulty or discrimination. Like the previously discussed study, they used images as part of the question stem that had to be interpreted to arrive at a correct answer.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Vorstenbosch et al () found increased item difficulty when using an image labeled format for students to select an answer to an item rather than selecting from a word list. Finally, Holland et al () found no difference in item difficulty or discrimination when using illustrated compared to text only vignettes in histology examinations. Other references to this line of inquiry are scarce, particularly in anatomical education although there does appear to be an increasing interest in this area.…”
Section: Introductionmentioning
confidence: 98%
“…Use of Images in Anatomy Assessment. Some studies have shown it makes no difference to test scores if images are included in the MCQ (Holland et al, 2015); others have found variable effects on item difficulty depending on the topic of the question (Vorstenbosch et al, 2013). Students' thought processes behind selecting the correct answer to MCQs with diagrams are described in Vorstenbosch et al (2014).…”
Section: Content Of Papers Selected For This Reviewmentioning
confidence: 99%
“…Of the 262 examination questions assessing material that was reinforced through active learning, a slight majority (60%) was associated with image‐based exercises. The percent correct and point serial correlation for each examination question were obtained from the university examination scoring service and were used to indicate examination item difficulty and discrimination (Holland et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Much of the previous work on visual and verbal formats have investigated the effects on learning in traditional, knowledge transmission settings (Butcher, ; Bartholomé and Bromme, ) or in assessments of learning (Hunt, ; Crisp and Sweiry, ; Berends and van Lieshout, ; Vorstenbosch et al, ; Holland et al, ). In this study, however, the effects of verbal and visual formats on learning were investigated in an active learning setting, in which students had time to think about their answers and discuss their answers with peers.…”
Section: Introductionmentioning
confidence: 99%